Synthesis, Characterization, and Fluorescence Studies of Novel Heterocyclic Azo Dyes Derived from Benzothiazole - Şener, Nesrin; Erişkin, Selinay; Şahin, Çiğdem; Yılmaz, Mehmet; Şener, İzzet (Wiley, 2017)
Ten novel fluorescent azo disperse dyes2a–e(open forms) and3a–e(closed forms) were obtained by the coupling reaction of carbocyclic amine based diazonium chloride with compounds2and3. The synthesized dyes were characterized by elemental analysis, high‐resolution mass spectrometry, Fourier transform infrared, and NMR spectral techniques. Moreover, we investigated the substituent effect and solvatochromic properties of the dyes on absorption and fluorescence spectra. At the same time, the absorption and emission spectral data of the closed form dyes3a–ewere compared with the open form dyes2a–edue to more planarity of the closed form dyes that lead to the extension of the π–electron conjugation.
Keywords: absorption spectroscopy; ethyl 3 (1,3 benzothiazol 2 ylamino) 3 hydroxy 2 (4' chlorphenylazo)acrylate; synthesis; ethyl 3 (1,3 benzothiazol 2 ylamino) 3 hydroxy 2 (4' methylphenylazo)acrylate; ethyl 3 (1,3 benzothiazol 2 ylamino) 3 hydroxy 2(phenylazo)acrylate; hydroxy 3 (4' chlorphenylazo) 4h pyrimido[2,1 b][1,3]benzothiazol 4 one; Article; hydroxy 3 (phenylazo) 4h pyrimido[2,1 b][1,3]benzothiazol 4 one; azo dye; hydroxy 3 (4' methylphenylazo) 4h pyrimido[2,1 b][1,3]benzothiazol 4 one; infrared spectroscopy; mass spectrometry; nuclear magnetic resonance spectroscopy; heterocyclic compound; elemental analysis; hydroxy 3 (4' nitrophenylazo) 4h pyrimido[2,1 b][1,3]benzothiazol 4 one; ethyl 3 (1,3 benzothiazol 2 ylamino) 3 hydroxy 2 (4' methoxyphenylazo)acrylate; hydroxy 3 (4' methoxyphenylazo) 4h pyrimido[2,1 b][1,3]benzothiazol 4 one; benzothiazole; fluorescence spectroscopy; unclassified drug; ultraviolet spectrophotometry; ethyl 3 (1,3 benzothiazol 2 ylamino) 3 hydroxy 2 (4' nitrophenylazo)acrylate; 16. Peace & justice; 3. Good health